Transmembrane TNF-dependent uptake of anti-TNF antibodies. Issue 4 (19th May 2017) - Deora, Arun; Hegde, Subramanya; Lee, Jacqueline; Choi, Chee-Ho; Chang, Qing; Lee, Cheryl; Eaton, Lucia; Tang, Hua; Wang, Dongdong; Lee, David; Michalak, Mark; Tomlinson, Medha; et al.
ABSTRACT: TNF-α (TNF), a pro-inflammatory cytokine is synthesized as a 26 kDa protein, anchors in the plasma membrane as transmembrane TNF (TmTNF), and is subjected to proteolysis by the TNF-α converting enzyme (TACE) to release the 15 kDa form of soluble TNF (sTNF). TmTNF and sTNF interact with 2 distinct receptors, TNF-R1 (p55) and TNF-R2 (p75), to mediate the multiple biologic effects of TNF described to date. Several anti-TNF biologics that bind to both forms of TNF and block their interactions with the TNF receptors are now approved for the treatment of a variety of immune-mediated diseases. Several reports suggest that binding of anti-TNFs to TmTNF delivers an outside-to-inside 'reverse' signal that may also contribute to the efficacy of anti-TNFs. Some patients, however, develop anti-TNF drug antibody responses (ADA or immunogenicity). Here, we demonstrate biochemically that TmTNF is transiently expressed on the surface of lipopolysaccharide-stimulated primary human monocytes, macrophages, and monocyte-derived dendritic cells (DCs) and expression of TmTNF on the cell surface is enhanced following treatment of cells with TAPI-2, a TACE inhibitor. Importantly, binding of anti-TNFs to TmTNF on DCs results in rapid internalization of the anti-TNF/TmTNF complex first into early endosomes and then lysosomes. The internalized anti-TNF is processed and anti-TNF peptides can be eluted from the surface of DCs. Finally, tetanus toxin peptides fused to anti-TNFs are presented by DCs to initiate T cell recall proliferation response. Collectively, these observations may provide new insights into understanding the biology of TmTNF, mode of action of anti-TNFs, biology of ADA response to anti-TNFs, and may help with the design of the next generation of anti-TNFs.